The British Islands / compiled from the latest Admiralty surveys, 1867 - Great Britain. Hydrographic Office (Great Britain. Hydrographic Office, 1872)
Depths shown by isolines and soundings.Relief shown by hachures and spot heights."Compiled & drawn by E.J. Powell, Hydrographic Office engraved by Davies & Bryer"--Lower margin."Published . Augt. 30th, 1867 . Corrections March 1872."[Admiralty chart] "2"--Lower right margin. Grayscale 1:1,700,000